Using activated charcoal to remove substances interfering with the colorimetric assay of inorganic phosphate in plant extracts - Dayrell, Roberta L. C.; Cawthray, Gregory R.; Lambers, Hans; Ranathunge, Kosala (Plant and soil, 2022)
Aim Organic substances in leaves of several southwest Australian native species interfere with sensitive colorimetric assays and prevent quantification of inorganic phosphate concentration ([Pi]). We aimed to develop a reproducible routine procedure for treating leaf extracts with activated charcoal (AC) to remove interfering substances, allowing the determination of [Pi] by the malachite green spectrophotometric assay. Methods Leaf extracts of native plants from southwest Australia in 1% ( v / v ) acetic acid were treated with 10 mg mL −1 acid-washed AC for removal of interfering substances. Standard solutions (0 to 18 μM Pi) with and without AC treatment were compared to quantify Pi loss. A spiking and recovery test was performed to validate the AC treatment. Results Leaf extracts treated with AC exhibited distinguishable absorbance peaks for the malachite green-orthophosphate complex between 630 and 650 nm, as opposed to untreated samples. The Pi-adsorption by AC represented a relatively larger fraction of [Pi] in solutions at 0–4 μM Pi range and stabilised at higher [Pi] when maximum adsorption capacity of AC reached at 11.7 μg Pi g −1 AC. The Pi recovery after AC treatment in spiked samples ranged between 100 and 111%. Conclusion The AC treatment successfully removed interfering substances from samples but caused Pi loss. Thus, quantification of [Pi] in AC-treated extracts requires sample [Pi] ≥ 6 μM Pi and the use of AC-treated standards. The error of the AC treatment was minor compared with environmental variability of leaf [Pi]. The AC treatment was a reproducible time- and cost-effective method to remove interfering substances from leaf extracts.